Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and bioactivity of novel triazole incorporated benzothiazinone derivatives as antitubercular and antioxidant agent - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Arkile, Manisha A.; Khedkar, Vijay M.; Jadhav, Nandadeep J.; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and M. bovis BCG, a small focused library of benzothiazinone based 1,2,3-triazoles has been efficiently prepared via click chemistry approach. Several derivatives were found to be promising inhibitors of MTB and M. bovis BCG characterized by lower MIC values (27.34-29.37 mu g/mL). Among all the synthesized compounds, 6c and 6e is the most active compound against MTB and M. bovis BCG. The compounds were further tested for anti-proliferative activity against HeLa, A549 and A431 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antioxidant activity with IC50 range = 14.14-47.11 mu g/mL. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target MTB DprE1, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of the in vitro and in silico study suggest that the triazole incorporated benzothiazinone may possess the ideal structural requirements for further development of novel therapeutic agents. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 3-Triazole; ADME prediction; Antioxidant; Antitubercular; Docking study

Synthesis and docking studies of pyrazine-thiazolidinone hybrid scaffold targeting dormant tuberculosis - Chitre, T. S.; Asgaonkar, K. D.; Miniyar, P. B.; Dharme, A. B.; Arkile, Manisha A.; Yeware, A.; Sarkar, Dhiman; Khedkar, Vijay M.; Jha, Prakash C. (Bioorganic & Medicinal Chemistry Letters, 2016)
The persistence of Mycobacterium tuberculosis (MTB) in dormant stage assists the pathogen to develop resistance against current antimycobactrial drugs. To address this issue, we report herein the synthesis of N-(4-oxo-2 substituted thiazolidin-3yl) pyrazine-2-carbohydrazide derivatives designed by following the molecular hybridization approach using pyrazine and thiazolidenone scaffolds. The compounds were evaluated against MTB H37Ra and Mycobacterium bovis BCG in dormancy model. Most of the compounds had IC50 values in 0.3-1 mu g/ml range. The active compounds were further tested for anti-proliferative activity against THP-1, Panc-1, A549, and MCF-7 cell lines using MTT assay and exhibited no significant cytotoxicity. We also report molecular docking studies using active analogs and MTB Decaprenylphosphoryl-beta-D-ribose-2'-epimerase (DprE1) to rationalize the biological activity and to provide an insight into the probable mechanism of action and binding mode of hybridized structures. The results obtained validate the use of molecular hybridization approach and also suggest that reported compounds can provide a novel pharmacophore to synthesize lead compounds against dormat MTB. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: docking; Dormant; Hybrid design; Pyrazine; Thiazolidenone; tuberculosis

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Synthesis and antitubercular activity of new thiazolidinones with pyrazinyl and thiazolyl scaffolds - Dhumal, Sambhaji T.; Deshmukh, Amarsinh R.; Khillare, Lalit D.; Arkile, Manisha A.; Sarkar, Dhiman; Mane, Ramrao A. (Journal of Heterocyclic Chemistry, 2017)
Emergence of multidrug resistant and extensively drug resistant tuberculosis has prompted to develop new molecular entities to treat the disease. A series of new 4-thiazolidinones with pyrazinyl and thiazolyl scaffolds has been synthesized, and their antitubercular activity is reported. The title 4-thiazolidinones, N-(pyrazinyl substituted thiazoloylamino)-2-aryl-4-thiazolidinones () have been first time prepared using pyrazinamide as a starting material via five successive steps. The purity and the structures of the intermediates (carboethoxythiazole, acid hydrazide, and azomethines) and title thiazolidinones () have been confirmed by TLC and spectral analyses, respectively. An antitubercular screening of the new 4-thiazolidinones has been performed on bacterial strains, Mycobacterium tuberculosis H37Ra and Mycobacterium BCG using the solutions of different concentrations of the compounds () and the screening results are presented. Compound has displayed notable antitubercular activity.

Synthesis of novel triazole-incorporated isatin derivatives as antifungal, antitubercular, and antioxidant agents and molecular docking study - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nawale, Laxman; Arkile, Manisha A.; Sarkar, Dhiman; Shingate, Bapurao B. (Journal of Heterocyclic Chemistry, 2017)
A library of 1,2,3-triazoles efficiently prepared via click chemistry and evaluated for their antifungal, antitubercular, antioxidant, cytotoxicity, molecular docking and ADME prediction.